Optimasi Strategi Marketing Mix untuk Meningkatkan Omzet UMKM CV Putra Tanjung Nganjuk - Muhamad Wildan Fawaid; Yopi Yudha Utama (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Marketing strategy is one way to win a sustainable competitive advantage for companies that produce goods or services. Marketing strategy can be seen as one of the bases used in compiling a company’s overall plan. In view of the breadth of the problems that exist within the company, it is necessary to have a comprehensive plan as a guide for the company’s segments in carrying out their activities, another reason that shows the importance of marketing strategy is the increasingly fierce competition in companies in general. This study has the aim of getting an overview of the marketing strategy to increase turnover, it is useful to overcome if there is a decrease in turnover and to find out how effective the implementation of the marketing strategy has been. This research was conducted at CV Putra Tanjung Nganjuk. Data collection techniques with documentation, interviews and observations, the type of descriptive research. The results of the analysis of the effectiveness of marketing strategies show an increase in total sales from year to year and serve as a reference for the effectiveness of marketing strategies in competition between companies